PREPARING FOR NEW LEARNING: PUBLIC VOCATIONAL HIGH SCHOOL STUDENTS’ AND TEACHERS’ E-LEARNING READINESS IN THE EFL INSTRUCTION - Aryani, Made Ayu Bintang; Santosa, Made Hery; Dambayana, Putu Eka (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2022)
This study aimed to find out 1) the e-learning readiness level of students and teachers in Public Vocational High School Singaraja and 2) factors affecting teachers’ and students’ e-learning readiness level of Public Vocational High School Singaraja. It designed using mixed method through survey instrument consists of 3 dimensions (e-learning readiness, e-learning acceptance, e-learning training) and interview guide. The instruments validated by the experts and gained 0.666 from 70 students’ sample and 0.231 from 7 teachers’ sample. The reliability was 0.988 0.666 of 35 items and 0.933 0.231 of 38 items. The survey filled by 410 students and 15 English teachers meanwhile the interview answered by 10 students and 5 English teachers. The questionnaires showed they still need few improvements meanwhile interview results shown their e-learning readiness affected by features, benefits, challenges, familiarity, experience and personal innovativeness. Those results showing that e-learning benefits improve their readiness meanwhile e-learning challenges could lower the users’ readiness. It is considered to improve their readiness by reducing e-learning challenges to create comfortable e-learning access.